Increased Risks of Spontaneous Bacterial Peritonitis and Interstitial Lung Disease in Primary Biliary Cirrhosis Patients With Concomitant Sjögren Syndrome. Issue 2 (January 2016) - Chen, Chun-Ting; Tseng, Yu-Chen; Yang, Chih-Wei; Lin, Hsuan-Hwai; Chen, Peng-Jen; Huang, Tien-Yu; Shih, Yu-Lueng; Chang, Wei-Kuo; Hsieh, Tsai-Yuan; Chu, Heng-Cheng
Abstract : Abstract: The incidence of Sjögren syndrome (SS) in primary biliary cirrhosis (PBC) patients is high. The influence of SS on the clinical outcomes of PBC patients, however, remains unclear. Our study retrospectively collected data on PBC-only patients and PBC patients with concomitant SS (PBC-SS) to compare the clinical differences of long-term outcomes between them. A total of 183 patients were diagnosed with PBC from January 1999 to December 2014 at our hospital. Of these, the authors excluded patients with diabetes, hypertension, advanced liver cirrhosis at initial diagnosis of PBC (Child–Turcotte–Pugh classification score of ≥7) and other liver diseases (ie, alcoholic liver disease, alpha-antitrypsin deficiency, viral hepatitis, and primary sclerosing cholangitis), and autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis. Of the remaining 125 patients, 77 (61.6%) were PBC-only and 48 (38.4%) were PBC-SS patients. The mean follow-up duration was 8.76 years. During the observation period, the incidence of interstitial lung disease was higher in the PBC-SS group than in the PBC-only group ( P = 0.005). The occurrence of spontaneous bacterial peritonitis was significantly different in PBC-SS patients than in PBC-only patients ( P = 0.002). The overall survival was lower in PBC-SS patients than in PBC-only patients ( P = 0.033). Although the incidence of hepatocellular carcinoma, end-stage renal disease, variceal bleeding, and hypothyroidism were all higher in the PBC-SS group than in the PBC-only group, the differences were not significant. Our study suggests that PBC-SS patients have a higher risk of developing interstitial lung disease and spontaneous bacterial peritonitis and have a poor prognosis. Aggressive surveillance of thyroid and pulmonary functions should therefore be performed in these patients.